Implementation of the Problem Based Learning Method in Improving Students' Fiqh Learning Outcomes at MA Negeri 2 Tulungagung - Masviyah, Farida (DEEP LEARNING: Journal of Educational Research, 2025)
This study aims to implement the Problem Based Learning (PBL) method to improve the learning outcomes of Fiqh in class XI students of MA Negeri 2 Tulungagung. The background of this study is the low learning outcomes of students in Fiqh, which is suspected to be due to conventional learning methods that are less innovative and do not actively involve students. PBL was chosen because it is considered capable of encouraging students to think critically, solve problems, and construct their own knowledge through case studies or contextual problems. This classroom action research (CAR) was carried out in two cycles. Data were collected through observations of teacher and student activities, learning outcome tests, and student response questionnaires. The results showed a significant increase in students' Fiqh learning outcomes after the implementation of PBL. In cycle I, the average learning outcomes showed an increase, and in cycle II, there was a further increase with the percentage of learning completion that had met the success indicators. In addition, student learning activities became more enthusiastic and participatory, and student responses to the PBL method were very positive. Thus, it can be concluded that the implementation of the Problem Based Learning method is effective in improving the learning outcomes of class XI students in MA Negeri 2 Tulungagung.